PERANAN SILEK GALOMBANG DALAM ACARA PESTA PERKAWINAN DI JORONG PANDAN KENAGARIAN TANJUNG SANI KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Kurnia Hidayati; Darmawati Darmawati; Herlinda Mansyur (FBS Universitas Negeri Padang, 2018)
Abstract This article was aimed to describe and explain role of Silek Galombang on wedding party in Jorong Pandan Kenagarian Tanjung Sani Kecamatan Tanjung Raya Kabupaten Agam. Type of this study was qualitative with analytical descriptive method. Technique of data collection were done by using library research, observation, interview and documentation. After collecting data, data were analyzed accurately and selected as needed and it’s relation with the posed problem. Result of this study showed that Silek Galombang was performed on wedding in Jorong Pandan and was a part of event on wedding party in that place. Roles of Silek Galombang were as medium of welcoming honorary guests, medium of tribute and medium of self-actualization on wedding party. Silek Galombang consisted of tagak alif motion, langkah suok, langkah kida, langkah suruik, langkah maju, balabek, maambek tagak itiak, simpia suok dan kida, simpia suruik, kudo-kudo langkah ampek, dan gerak sambah. The dancer number of Silek Galombang were 7-9 dancers, 1 dancer as Tuo silek (teacher). This dance was divided into 2 groups with face to face position. 1 group represented the guest and the other one represented the party organizer. Silek Galombang was performed at street in front of the party organizer house during the day. Keywords: Roles, Silek Galombang, Wedding Party